Pengaruh Promosi Kesehatan terhadap Tingkat Pengetahuan Mengenai Covid-19 pada Pasien Rawat Jalan Rumah Sakit X - Denissa Kristalin Hermandia; Ai Susi Susanti (Jurnal Health Sains, 2021)
Since the discovery of COVID-19 cases in Indonesia in early March 2020, the number of COVID-19 transmission in Indonesia has increased. COVID-19 is a virus that causes diseases ranging from mild and severe symptoms, this disease attacks the respiratory system, the disease is in the spotlight because of its first appearance in 2019 in Wuhan, China. This study aims to analyze the influence of health promotion on the level of knowledge about covid-19 in hospital outpatients x. This study uses a type of quantitative research using pseudo-experimental methods or post-test (Questionnaire). The results of the frequency of Prevention Knowledge conducted on patients in hospitals "X" are influenced by the granting of interventions to increase knowledge in outpatients regarding the prevention of COVID-19. This counseling activity is carried out so that communication can be received and health messages can be delivered. So that it can help in increasing the target knowledge about COVID-19 prevention. Conclusion there are differences in prevention of 6M about COVID-19 at the time before being given counseling and after giving / conducted counseling. This means that there is an influence of health promotion on the level of knowledge about COVID-19 and the prevention of 6M in hospitals " X ".